Вождь краснокожих и другие новеллы - О. Генри (Читаем в школе, 2017)
Экземпляры: ф9 (20190514) / Инвентарный номер: 57801 / Цена: 96.00 / Сис.шифр: И(англ)ср / Авт.знак: О-36 / ГРНТИ: 17.82 / ББК: 84(7Сое)